2021
DOI: 10.1017/ice.2021.80
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial stewardship programs in adult intensive care units in Latin America: Implementation, assessments, and impact on outcomes

Abstract: Objective: To assess the impact of antimicrobial stewardship programs (ASPs) in adult medical–surgical intensive care units (MS-ICUs) in Latin America. Design: Quasi-experimental prospective with continuous time series. Setting: The study included 77 MS-ICUs in 9 Latin American countries. Patients: Adult patients admitted to an MS-ICU for at least 24 hours were included in the study. Methods: This multicenter study was conducted over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…concluded that antimicrobial stewardship programs (ASPs) helped to reduce the use of antifungals in hospitalized patients and highlighted the importance of promoting antifungal stewardship among antibiotic stewardship [20]. Also, Rodolfo E. Quirós et al showed significant improvement in antimicrobial utilization after multiple and intensive ASPs [3] . Interestingly, targeting antimicrobial therapy to likely pathogens was not mostly considered a factor that may help control AMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…concluded that antimicrobial stewardship programs (ASPs) helped to reduce the use of antifungals in hospitalized patients and highlighted the importance of promoting antifungal stewardship among antibiotic stewardship [20]. Also, Rodolfo E. Quirós et al showed significant improvement in antimicrobial utilization after multiple and intensive ASPs [3] . Interestingly, targeting antimicrobial therapy to likely pathogens was not mostly considered a factor that may help control AMR.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial agents have the advantage of treating infectious diseases, and they have the potential not only to retain the quality of life of the patient but have also proved to be lifesaving in a variety of severe infectious conditions [1]. Improper use of antimicrobials has led to the development of antimicrobial resistant (AMR), which has been associated with failure in managing infections, increased in length of hospital stay, increased mortality, morbidity [2,3] , and health costs [4,5 ]. Several factors have been described in the literature to be correlated with inappropriate prescribing of antimicrobials, such as physicians with less experience, level of knowledge, uncertain diagnosis, and patient caregiver influences on physician's decision [6].…”
Section: Introductionmentioning
confidence: 99%
“…11,32 Vancomycin is an agent that must be handled correctly due to the high rates of methicillin-resistant S aureus infections in the area. 12 Ertapenem presented one of the most significant improvements in its empirical use. This behavior can also respond to the attention that has been given to promoting the reduction of the unnecessary use of this antibiotic within the hospital through the different group educational sessions developed.…”
Section: Enterococcus Faecalis 35 44mentioning
confidence: 99%
“…10 An example of such a practice is known as "Handshake Stewardship" (HS), characterized by having no antibiotic restrictions or prior authorizations, but a daily prescription monitorization, and having direct communication with physicians. 11 Implementing AMS in Latin America has been challenging, because of strong opposition by prescribers, 12,13 limited resources, 14 which may include, a lack of financial support from hospital administrators, lack of information and technology development, 12 and the need for adequate trained hospital staff in infectious diseases, such as nurses and pharmacists, especially infectious diseases clinical pharmacists. 3,13 Hospital Clínica Bíblica is one of the leading private hospitals in Costa Rica and Latin America, where the development of clinical pharmacy initiatives within the hospital, has proven not to be only a key element for patient safety and clinical outcomes, but also a contribution to the development of clinical pharmacy in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial resistance represents a serious problem in Peru because over 50% of Gramnegative bacteria isolated are Escherichia coli and Klebsiella pneumoniae ESBL across different hospitalization areas, including general rooms, emergency rooms and intensive care units [13]. In response to the antimicrobial resistance challenge, some Peruvian hospitals have started the implementation of antimicrobial stewardship (AMS) programs in order to reduce the consumption of broad-spectrum antibiotics [13,14]. These response strategies include antimicrobial restriction, educational campaigns and promotion of antimicrobial profiles and algorithms, prospective audit, pre-authorized forms and monitoring empirical antimicrobial treatment flowcharts elaborated in consensus with the intensive care, infection control, pharmacy and microbiology units [13].…”
Section: Introductionmentioning
confidence: 99%